Experimental and Numerical Study on Thermal Performance of a Novel Direct Expansion Air-Source Heat Pump Heating System - Wang, Haobo; Cheng, Yuanda; Wang, Dawei; Peng, Weijin; Ai, Zejian; Jia, Jie; Duan, Pengfei; Yang, Jinming (Frontiers in Energy Research, 2022)
In this paper, a novel direct expansion air-source heat pump heating system with a gravity-driven radiator as a heating terminal was developed, for the purpose of reducing the energy consumption and improving the thermal comfort of indoor personnel. The thermal response speed of the system at the start-up stage was experimentally studied firstly. The results showed that the thermal response speed of the developed system was slightly lower than that of a traditional air-source heat pump heating system with a convective heating terminal, but largely higher than that of an air-source heat pump floor radiant heating system. When the outdoor air temperature fluctuated between −5.2℃ and −1.0℃, the average rising ratios of indoor air temperature at the start-up stage for the developed heating system and the traditional system are 10.8℃/h and 13.8℃/h respectively. On this basis, an optimization study was then conducted to further improve the thermal performance of the developed heating system. The numerical results indicated that integrating a cross-flow fan to the gravity-driven radiator is able to promote the thermal performance of the heating system obviously at the start-up stage, because the convection heat transfer of the radiator was highly enhanced. Among the simulation conditions, the time required for the air temperature at head height to reach the designed temperature is shortest when the flow angle of the fan is 0° with an air speed of 0.6 m/s. while setting the flow angle of the fan to −45° with an air speed of 0.4 m/s is recommended to achieve the most thermal comfort for the whole body.